The Environmental Responsibilities of Food Service Establishments in Nabua, Philippines - Maria Joy I. Idian; Louraine T. Florendo; Princess Mae Ll. Tagum; Godwin Kim Z. Zamudio (The Indonesian Institute of Science and Technology Research, 2022)
Food service industry needs to observe and adopt existing and new environmental practices that are beneficial for the environment preservation and the conservation of natural resources on which they hugely depend to operate. With this, the purpose of this thesis is to assess the responsiveness of food service establishments specifically the local eateries or cafeterias in Nabua, Camarines Sur towards their environmental responsibilities. The study covers the demographic profile of the respondents and the business profile, the rate of environmental practices being observed by the establishments along: energy efficiency and conservation, water efficiency and conservation, recycling and composting, pollution prevention, and food packaging. These were the problems being encountered in observing these practices and the recommendations which are formulated based from the findings. At this moment in time, the food service industry has tended to be slower to adopt environmental practices than other segments of the hospitality industry, however are currently following suit and are adopting practices that are beneficial for the environment and reduce the negative impacts. To collect data and information, descriptive method was used and survey and informal interview were conducted. The respondents are the business owners and employees of eighteen selected food service establishments. The result showed that these establishments are highly observing environmental practices on the areas of pollution prevention, recycling and composting in observance with the existing ordinances. However, some of the practices in energy efficiency and conservation, water efficiency and conservation, and food packaging still has to be recognized and improved. Also, it was revealed that financial capacity is a big factor in observing such environmental practices. Nevertheless, with more information education campaign programs and activities implemented by the municipality and other concerned government agencies, food service operators will further deepen their understanding and intensify commitment to environmental initiatives within business.